Isolated vitamin D supplementation improves the immune-inflammatory biomarkers in younger postmenopausal women: a randomized, double-blind, placebo-controlled trial - Bueloni-Dias, Flavia Neves [UNESP]; Orsatti, Claudio Lera [UNESP]; Cangussu, Luciana Mendes [UNESP]; Poloni, Priscila Ferreira [UNESP]; Spadoto-Dias, Daniel [UNESP]; Nahas-Neto, Jorge [UNESP]; Nahas, Eliana A. P. [UNESP] (Lippincott Williams & Wilkins, 2018)
Objective:The aim of this study was to evaluate the effect of vitamin D (VitD) supplementation on immune-inflammatory biomarkers in younger postmenopausal women.Methods:In this double-blind, placebo-controlled trial, 160 postmenopausal women aged 50 to 65 years with amenorrhea 12 months were randomized into two groups: VitD group, oral supplementation with 1000IU VitD(3)/day (n=80) or placebo group (n=80). The intervention time was 9 months, and the women were assessed at baseline and endpoint. Serum levels of interleukins (ILs)-1, IL-5, IL-6, IL-10, IL-1270, IL-17, tumor necrosis factor-alpha, and interferon-gamma were determined by immunoassay. Plasma concentrations of 25-hydroxyvitamin D [25(OH)D] were measured by high-performance liquid chromatography. Per-protocol analysis was adopted as the statistical method using a gamma distribution and repeated measures design, followed by Wald's multiple comparisons test.Results:The two groups were similar at baseline in terms of clinical and laboratory parameters. After 9 months, there was a significant increase of 25(OH)D levels in the VitD group (+45.4%, P<0.001) and a decrease (-18.5%, P=0.049) in the placebo group. A significant decrease in IL-5, IL-12p70, IL-17, tumor necrosis factor-alpha, and interferon-gamma levels was observed in the VitD group (P<0.05). IL-5 and IL-6 levels were significantly lower in the VitD group compared to the placebo group (P<0.05). There were no significant intervention effects on serum IL-1 or IL-10 levels in either group (P>0.05).Conclusions:In younger postmenopausal women, isolated supplementation with 1000IU of VitD(3) for 9 months was associated with a reduction in proinflammatory biomarkers.
Keywords: Cytokines; Immune-inflammatory markers; Menopause; Vitamin D